The Impact of Energy Consumption on Economic Development in North Africa: A Long-Term Dynamics Analysis Using the ARDL Approach - Zahir, Allal; Aarich, Zineb; Oubahou, Yassine; Bouazid, Hassan; Rehaimi, Hassan; Elouafa, Khalid (International Journal of Energy Economics and Policy, 2025)
This article examines the relationship between economic development and renewable energy consumption in North Africa. The main objective is to analyze the impact of this consumption on economic growth in this region, taking into account other macroeconomic variables. To do this, we use data covering the period from 1990 to 2023 and apply the Autoregressive Distributed Lag (ARDL) model to explore the short- and long-term dynamics between the variables studied. Empirical results reveal that renewable energy consumption and inflation have a negative and statistically significant effect on economic development. In contrast, investment and trade openness exert a positive and significant influence on the latter. These results highlight the importance of a well-managed energy transition. They suggest that public authorities should strengthen policies promoting the adoption of renewable energies, while ensuring their effective integration into the economic fabric to maximize their positive impact on growth.